Exploring the correlation between translation methods and quality in Mandarin-Indonesian: A case study - Supriyadi, Francisca Akhidnasiwi; Junining, Esti; Yulianto, Wawan Eko (Universitas Ahmad Dahlan, 2024)
This study examines how approaches affect the quality of translating the Mandarin children's narrative